Toledo. Urban planning and speculation in historial cities - M. Antonio Zárate Martín (Anales de Geografía de la Universidad Complutense, 2008)
Toledo is a city integrated by residential differentiated areas because the nature of the emplacement, the inheritance of the past, the protection criteria of the historical patrimony, the urban development programmes and the most recent urban policy. These residential areas are badly connected. Nevertheless, these circumstances have contributed that the historic core has come up to us well preserved. Precisely, this it was the reason that allowed the classification of Toledo in 1986 in the “World Heritage List of the Cities Patrimony of the Humanity”. Today, the patrimonial and environmental values of Toledo are threatened by a Municipal Planning Scheme that proposes the urbanization of the fertile plaines of the Tagus to integrate the different pieces of the city. In the practice, Toledo traverses the risk of turning into an outer suburb of the agglomeration of Madrid and, at best, into a “ thematic park of the history ”. The problems of cohesion of the city will see more aggravated that solved.